Synthesis of carbon nanotubes with chemical vapor deposition by using milled iron catalyst - Guler, Omer; Evin, Ertan; Guler, S. Hale (Natl Inst Optoelectronics, 2013)
In this study, carbon nanotubes were synthesized by chemical vapor deposition (CVD) process. In CVD process, milled iron powders were used as catalyst. Initially, iron powders were milled by high energy ball mill for 3h. Then, iron particles were homogeny distributed onto substrate and carbon nanotubes were obtained by CVD process inside tube reactor. Carbon nanotubes were investigated by HR-TEM to determine the effect of milled iron catalyst on nanotube formation.
Keywords: Carbon nanotubes; Chemical vapor deposition; catalyst